EVALUASI IMPLEMENTASI PENYALURAN PROGRAM INDONESIA PINTAR (PIP) BAGI SISWA KURANG MAMPU - Septiandika, Verto (PEDAGOGY, 2017)
This research aims to evaluate the implementation of the delivery of Program Indonesia Pintar (PIP) for underprivileged students at SDN Jrebeng Wetan Year 2016. The subject of this research is the recipient of Bantuan Siswa Miskin (BSM) or  PIP Stage 3.8 and 11 of 2016. The object of this research is the program of BSM or PIP Stage I of 2016. This research uses a qualitative approach with data collection techniques include observation, interviews, and documentation. Based on the results of data analysis can be concluded that the implementation of the distribution of funds in SDN Jrebeng Wetan Year 2016 is appropriately channeled to the parents of students who can not afford but the utilization is still less than optimal for student needs. Meanwhile, the impact felt by teachers of this program increased student achievement and activeness is increasing despite the constraints that often faced the administration in obtaining this fund.